With age comes …? An examination of gendered differences in the resource advantages associated with parental age in Norway - Wendy Sigle; Øystein Kravdal (Comparative Population Studies (CPoS), 2021)
Using high-quality register data, this paper constructs an empirical portrait of older parenthood in contemporary Norway and explores gender differences in the extent to which older parents are better-resourced parents. Like most family issues, academic and policy discussions of older parenthood have tended to focus on the experiences of women. Although motherhood at older ages was not uncommon in previous generations, rapid social and family changes in recent decades mean that today's older mother is far more likely to be having her first child. She may have focused on obtaining a good education and then on establishing her career and finding a supportive partner. When viewed through this motherhood lens, older parents are often portrayed as being relatively well-off financially and enjoying stable family lives. Viewed through the fatherhood lens, however, the family literature suggests that age might not be as strong a marker of socio-economic advantage. Our findings show that this is the case: While older fathers are, on average, more socio-economically advantaged than younger fathers around the time their children are born, their relative advantage is narrower than what we observe when older mothers and younger mothers are compared. Gender differences in the family history profiles of older parents appear to explain some of the differentials we document. The children of older fathers are more likely to be born into blended families and less likely to born to a mother who postponed her first birth than are the children born to older mothers. The results suggest that the meaning of paternal age and maternal age differs: paternal age is not as strong a marker of socio-economic advantages and resources for children as maternal age is.
urn:nbn:de:bib-cpos-2021-13en5
Keywords: 300; Family Diversity; Fathers; Fertility postponement; Late parenthood; Norway